The constrains of using the technologies of the augmented reality in teaching English from the point of view of the teaching staff at the colleges of languages and translation of Najran University - Al Hudaisan, Amal Hamad Rashid (Journal of Curriculum and Teaching Methodology, 2024)
This study aimed to identify the obstacles to using augmented reality techniques in teaching English from the point of view of faculty members at the Colleges of Languages and Translation at Najran University in the Kingdom of Saudi Arabia. To achieve this, the researcher used the descriptive-analytical approach. The questionnaire was used as a main tool for collecting data from the members of the study community, and a random sample was selected consisting of (38) members of the faculty of the faculties of languages and translation. (16) Paragraph.As for the second axis, the results indicated several solutions and proposals to overcome the obstacles to using augmented reality technologies in teaching the English language in the colleges of languages and translation at Najran University from the point of view of the study sample. These solutions and proposals included holding training courses for using augmented reality technologies and providing the necessary technologies for using augmented reality. Enhancing the confidence of faculty members, encouraging and motivating them to learn and master the skills of using augmented reality technologies in teaching female students, and addressing the problems they face in using augmented reality technologies in teaching female students.
Keywords: Obstacles; augmented reality; teaching English; colleges of languages and translation; Najran University; educational technologies